The relationship between perch type and aggressive behavior in the lizard Norops polylepis (Squamata: Dactyloidae) - Jiménez, Randall R. (2015)
The intensity of aggression against intruders by owners of a territory has been related to the type of resources available to an individual within its territory. The influence of perch-site characteristics on aggressive behaviour of resident male Norops polylepis in presence of an intruder male was investigated in this study. At each perch site, pairwise encounters were conducted in which the aggressive behavior of resident males was recorded, along with the diameter of the perch and the number of nearby perches. Aggressive behavior of resident males increased on larger perches and to some extent in areas having greater density of nearby saplings. Potential explanations for the high aggressive behavior of N. polylepis on broad perches with high number of neighboring saplings are explored.